Hate Speech Discourse on Platform X (Twitter): A Critical Discourse Analysis - Nurdelia Nasution; Intan Nia Salsabila; Meisya Audreyanna; Saralena Manik; Christy Aulia Simanjuntak; Muhammad Natsir (Universitas Palangka Raya, 2026)
The phenomenon of hate speech on social media, particularly on platform X, has intensified alongside the increasing level of public interaction within open and largely unregulated digital spaces. This condition not only generates communicative conflicts but also shapes complex social experiences for individuals, particularly in relation to identity, emotion, and power relations. This study aims to gain an in-depth understanding of how hate speech is constructed, interpreted, and negotiated by users within the context of digital interaction. Employing a qualitative approach with a Critical Discourse Analysis (CDA) design, data were collected through in-depth interviews, non-participant observation, and digital document analysis involving 10–15 active users of platform X who have experienced hate speech. Data were analyzed thematically by identifying patterns of meaning emerging from participants’ experiences. The findings reveal three major themes: hate speech as a lingering yet normalized emotional experience; discourse as a site for the reproduction of power and identity delegitimization; and self-negotiation strategies employed by participants to survive within digital spaces. These findings indicate that hate speech operates not only at the linguistic level but also in shaping users’ social and psychological realities. Theoretically, this study reinforces Critical Discourse Analysis by emphasizing the importance of subjective experience in interpreting discursive practices. Practically, it contributes to the development of digital literacy, content moderation policies, and efforts to create more inclusive and reflective communication spaces in the digital era.